Influences on decision-making for young women undergoing bilateral prophylactic mastectomy - Glassey, R.; O'Connor, Moira; Ives, A.; Saunders, C.; Hardcastle, Sarah (Elsevier Ireland Ltd., 2017)
© 2017 Elsevier B.V. Objective: The objective of this study was to explore the influences on decision-making of younger women ( < 35) undergoing or considering bilateral prophylactic mastectomy (BPM). Methods: Qualitative interviews guided by interpretative phenomenological analysis (IPA) were conducted with forty-six women who had a strong family history of breast cancer (BC) who had either undergone (n = 26) or were considering (n = 20) BPM. Participants were recruited from Australia and New Zealand (NZ) via hospitals, a genetics clinic, a research cohort, a registry and online. Results: Four themes underpinning the influences on decision-making were identified: fear and anxiety, children, personal experiences with BC, health professional's influence. Conclusions: The decision to undergo BPM for younger women ( < . 35) was multifaceted, however, it appeared that fear and anxiety were the main influence. Younger women appear more anxious than previous research with older women. There appears to be few differences between those with confirmed BRCA1/2 mutations and those with no known mutation and this is clinically significant. Practice implications: These findings have important practice implications, particularly improving communication of risk statistics, especially to those with no known mutation. Health professionals need to take into account the way younger women perceive information given to them when discussing risk.